2018
DOI: 10.1002/ejp.1213
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the improvement of fatigue in fibromyalgia: A 4‐week left dorsolateral prefrontal cortex repetitive transcranial magnetic stimulation randomized‐controlled trial

Abstract: This study provides evidence that 4-weeks of daily rTMS to the left DLPFC is able to improve fatigue in fibromyalgia. This novel finding provides impetus for the further investigation of the utility of TMS approaches for the relief of fatigue, an otherwise difficult-to-treat symptom, in fibromyalgia and related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 57 publications
0
41
0
1
Order By: Relevance
“…Fitzgibbon et al . recently noted the significant improvement of fatigue and the greater chance in reducing pain intensity in active than sham rTMS targeting the left DLPFC .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Fitzgibbon et al . recently noted the significant improvement of fatigue and the greater chance in reducing pain intensity in active than sham rTMS targeting the left DLPFC .…”
Section: Discussionmentioning
confidence: 97%
“…39,40 Fitzgibbon et al recently noted the significant improvement of fatigue and the greater chance in reducing pain intensity in active than sham rTMS targeting the left DLPFC. 29 Another recent meta-analysis showed that rTMS for fibromyalgia patients trended toward reducing pain intensity but did not alter depressive symptoms. 41 That meta-analysis consisted of only one study using stimulation at the DLPFC and four studies using stimulation at the M1 area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in pain ratings do not permit inferring which of the sensory, cognitive, or affective dimensions of pain was preferentially modulated by tDCS. Accumulating evidence suggests that the beneficial effects of noninvasive cortical stimulation may derive from activity changes in high-order brain areas [3,4,10], and that analgesic effects may emerge as secondary to the modulation of emotion-related neural networks distant from the stimulated point [34]. In accordance with this, a strict somatotopic relation between the painful region and the cortical motor area stimulated may not be mandatory [22].…”
Section: Discussionmentioning
confidence: 99%
“…Bei chronisch myofaszialem Schmerz zeigt HF-rTMS/M1 eine signifikante Schmerzlinderung um 30 % und eine signifikante Reduktion der Analgetikaeinnahme um 45 % [68], was durch eine zwei-te Studie bestätigt wurde [69]. Bei Fibromyalgie zeigt HF-rTMS/ DLPFC links eine günstige Wirkung auf das Fatigue-Syndrom [70]. In einer anderen Studie wurde wiederum nur über eine analgetische Wirkung von HF-rTMS/DLPFC links, aber nicht über eine Verbesserung der Müdigkeit oder Schlafqualität bei Fibromyalgie berichtet [71].…”
Section: Fibromyalgie Und Andere Chronische Schmerzsyndromeunclassified